The effect of parent–adolescent relationship quality on deviant peer affiliation: The mediating role of self-control and friendship quality. (October 2020) - Liu, Fangsong; Chui, Harold; Chung, Man Cheung
Previous research demonstrated the association between parent–adolescent relationship quality and deviant peer affiliation, but it is unclear whether this relation is mediated by other psychological and interpersonal variables, whether father– and mother–adolescent relationship quality have different pathways in predicting deviant peer affiliation, and whether gender moderates these associations. A sample of 543 students from grades 10 to 12 (42.7% male; age M = 16.2 years, SD = 1.0) was selected from a Chinese high school in Shenzhen, China. They provided demographic variables and completed self-report measures of father– and mother–adolescent relationship quality, self-control, friendship quality, and deviant peer affiliation. The results showed that lower father–adolescent relationship quality was associated with lower self-control, which in turn was associated with higher deviant peer affiliation. Mother–adolescent relationship quality did not have direct or indirect association with deviant peer affiliation. In addition, male and female adolescents had no significant difference in the associations between father– and mother–adolescent relationship quality, self-control, friendship quality, and deviant peer affiliation. Implications and limitations of these findings were discussed.